Functional deletion of the calcium-sensing receptor in a case of neonatal severe hyperparathyroidism - Ward, Bryan K; Magno, Aaron L; Davis, Elizabeth A; Hanyaloglu, Aylin C; Stuckey, Bronwyn G A; Burrows, Mark; Eidne, Karin A; Charles, Adrian K; Ratajczak, Thomas (The journal of clinical endocrinology and metabolism, 2004)
Heterozygous inactivating mutations of the calcium-sensing receptor (CaR) cause familial hypocalciuric hypercalcemia, whereas homozygous or compound heterozygous inactivating mutations normally cause neonatal severe hyperparathyroidism. In a case of neonatal severe hyperparathyroidism characterized by moderately severe hypercalcemia and very high PTH levels, coupled with evidence of hyperparathyroidism and effects on brain development not previously demonstrated, we detected point mutations on separate alleles of the CaR, resulting in premature stop codon substitutions at G94 and R648. This led to severely truncated receptors and an effective so-called knockout of functional CaR. FLAG-tagged, truncated receptors were expressed in HEK293 cells for functional analysis. Confocal microscopy demonstrated cytoplasmic localization of the G94stop receptor, whereas the R648stop receptor was present both in the cytoplasm and associated with the cell membrane. Only the R648stop receptor could be detected by Western analysis. Functional assays in which R648stop and wild-type receptor were cotransfected into HEK293 cells demonstrated a reduction in wild-type Ca(2+)-responsiveness by the R648stop receptor, even at physiological Ca(2+) levels, thus simulating familial hypocalciuric hypercalcemia in relatives of the infant who were heterozygous for the R648stop mutation. The R648stop receptor alone was nonresponsive to Ca(2+). This case contributes to our understanding of the clinical manifestation of a CaR knockout.